1994
DOI: 10.1002/acp.2350080410
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward a middle ground on the ‘false memory debate’: Reply to commentaries on lindsay and read

Abstract: This rejoinder to the six commentaries on Lindsay and Read (this issue) focuses primarily on responding to criticisms levelled by some of the commentators, We clarify and elaborate upon the grounds for believing that some mental health practitioners use highly suggestive memory recovery therapies and that such therapies can lead some clients to develop illusory memories or false beliefs about childhood sexual abuse. 'We also comment on Pezdek's ideas concerning signal detection theory, Morton's application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…This comment reinforces the important distinction Read and Lindsey (1994) make between beliefs and memories in relation to the phenomenon of recovered memories. A person can develop the belief that he or she has been sexually abused without having any memory of it.…”
Section: Discussionsupporting
confidence: 68%
“…This comment reinforces the important distinction Read and Lindsey (1994) make between beliefs and memories in relation to the phenomenon of recovered memories. A person can develop the belief that he or she has been sexually abused without having any memory of it.…”
Section: Discussionsupporting
confidence: 68%
“…These findings were similar to previous research that has shown significant inconsistencies in reports over time (Offer, et al, 2000) and variations in the extent of accuracy over time by topic (Henry, et al 1994). In addition, studies have shown that people's perceptions and interpretations of events change over time as their lives unfold (Read & Lindsay, 1994). As noted by Brewin, Andrews, and Gotlib (1993, p. 941, the accuracy of recall of physical abuse is threatened by social influences, childhood amnesia, and the simple fallibility of memory.…”
Section: Discussionsupporting
confidence: 89%
“…This type of data would be reliable but not valid. Unreliability, or the inconsistency of a response between two measurement occasions, can occur for a number of reasons: the clarity of a memory can fade over time; personal memories rarely contain information about absolute time; individuals may redefine or reconstruct their past based on their current circumstance or influences from other people, such as therapists or siblings; appraisals of meanings of behavior may change over time (Loftus, 1982(Loftus, , 1996Aneshensel, Estrada, Hansell, & Clark, 1987;Read & Lindsay, 1994;Ceci & Bruck, 1996;Golub, et al, 2000;Schraedley, Turner, & Gotlib, 2002;Hardt & Rutter, 2004).…”
mentioning
confidence: 99%
“…Instead, they are often a fusion of imagined, real and suggested information (Lindsay & Read, 1995;Read & Lindsay, 1994;Wade, Garry, Read, & Lindsay, 2002).…”
Section: Distinguishing Between "Memory Flaws" and "False Memories"mentioning
confidence: 99%